Documentary inventory as a tool on dissemination of cultural heritage (Ágora de Heterodoxias, 2020)
Using Cultural Heritage, Movable and Property Cultural Heritage, Documentary Inventories and finally Diffusion of Movable Cultural Heritage as categories, this study focused on a qualitative approach, of a descriptive type, with a documentary research method. In addition, uses techniques such as observation and documentary analysis were used and the instruments were two matrices, one of them the categorial matrix and the other a comparative matrix. Aspects such as the structure of the formats, the profile of who prepares the inventories, the phases of elaboration of them, their uses, their accessibility, their dissemination and the good practices used in Colombia, Spain and the United States were analyzed. The results of the instruments reveal that the structure of the formats does not have an understandable vocabulary for the users, it is not easy for a citizen to access the information since they have to subscribe in the databases of the entities that administer the heritage.
Keywords: Dissemination of cultural heritage; Movable Cultural Heritage; Documentary Inventory